Effectiveness of nonprofit organisations / Hasnatulsyakhira Abdullah Hadi ... [et al.] - Abdullah Hadi, Hasnatulsyakhira; Bakar, Ahmad Naqiyuddin; Zainon, Saunah; Mohd Noor, Nurul Hidayana (2021)
Nonprofit organisations (NPOs) are increasingly demanded from time to time to demonstrate their effectiveness (Carman, 2010; Ebrahim & Rangan, 2010; Popa, 2014). There is no specific definition of organizational effectiveness. Various scholars in this field also have different perspectives in defining nonprofit organisations (NPOs) effectiveness. Organisational effectiveness is the extent to which an organisation has met its stated goals and objectives and how well it performed in the process (Porbeni, 2016; Wadongo, 2014; Yankey & McClellan, 2003). Other scholars defined effectiveness as operational effectiveness, integrity, social responsibility, and success (Walsh & Lenihan, 2006). Initially, organisational effectiveness is a part of organisational performance (Lee & Choi, 2003; Mohd Noor, 2017). In addition, organisational effectiveness is also subjective on what the organization thinks about effectiveness. When the conceptualization of an organisation changes, this also will change the definition of effectiveness, the characteristics used in measuring its effectiveness, and the theory or framework that explains it (Cameron, 2014). As being non-profit-oriented, the effectiveness of NPOs cannot be solely based on financial performance. NPOs must pay attention to the effectiveness of the organisation as it ensures its survival. In this paper, the different approach of organizational effectiveness is explained and the most compatible approach to be used by NPOs is highlighted. These four approaches are being selected as according to Balduck and Buelens (2008), the fundamental of effectiveness in organizations revolves around them which are goal approach, system resource, internal process, and strategic constituency and based on four-criteria model was developed by Cameron (1980 & 1986). These elements are those that define how well an organization performs in the field and the elements balance all important aspects needed for the survival of the organization (Lecy, Schmitz, & Swedlund, 2012; Liket & Maas, 2015). These approaches are prominent in this field and have been studied extensively (Balduck & Buelens, 2008; Cameron, 2014; Connolly, Conlon, & Deutsch, 1980; Forbes, 1998; Moxham, 2014; Papadimitriou et al., 2007) and some of their elements are being applied in the multi-dimensional approach that has been agreed by many scholars (Ashraf & Abd Kadir, 2012; Lecy et al., 2012; Liket & Maas, 2015; Moxham, 2014; Wadongo, 2014).